Abnormal Near‐Infrared Absorption in 2D Black Phosphorus Induced by Ag Nanoclusters Surface Functionalization. Issue 43 (24th August 2018) - Hu, Zehua; Li, Qiang; Lei, Bo; Wu, Jing; Zhou, Qionghua; Gu, Chengding; Wen, Xinglin; Wang, Junyong; Liu, Yanpeng; Li, Shisheng; Zheng, Yue; Lu, Junpeng; et al.
Abstract: Black phosphorus (BP), as a fast emerging 2D material, shows promising potential in near‐infrared (NIR) photodetection owing to its relatively small direct thickness‐dependent bandgaps. However, the poor NIR absorption due to the atomically thin nature strongly hinders the practical application. In this study, it is demonstrated that surface functionalization of Ag nanoclusters on 2D BP can induce an abnormal NIR absorption at ≈746 nm, leading to ≈35 (138) times enhancement in 808 (730) nm NIR photoresponse for BP‐based field‐effect transistors. First‐principles calculations reveal that localized bands are introduced into the bandgap of BP, serving as the midgap states, which create new transitions to the conduction band of BP and eventually lead to the abnormal absorption. This work provides a simple yet effective method to dramatically increase the NIR absorption of BP, which is crucial for developing high‐performance NIR optoelectronic devices. Abstract : The near‐infrared absorbance of black phosphorus is enhanced via a new strategy of silver nanoclusters functionalization. Theoretical calculations reveal that new midgap states are introduced in this process, thus activating a new optical transition route.